2021
DOI: 10.3390/ijerph18136892
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Coordinated Blood Pressure Telemonitoring for Urban Hypertensive Patients: A Systematic Review and Meta-Analysis

Abstract: Coronavirus disease 2019 (COVID-19) has put hypertensive patients in densely populated cities at increased risk. Nurse-coordinated home blood pressure telemonitoring (NC-HBPT) may help address this. We screened studies published in English on three databases, from their inception to 30 November 2020. The effects of NC-HBPT were compared with in-person treatment. Outcomes included changes in blood pressure (BP) following the intervention and rate of BP target achievements before and during COVID-19. Of the 1916… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Four of the studies reported including experienced nurses in the field of chronic disease management [ 6 , 30 , 31 , 33 ], one included a nurse manager [ 34 ], two studies highlighted the need to have the nurses go through a special course on cultural competency [ 32 ] and formal training on telephone health coaching [ 35 ] prior to participating in the study. Other studies have reported that Registered Nurses (RN) have the undergraduate preparation to promote healthy lifestyles, prevent the development of disease and deliver care and follow-up to different health conditions on community heath setting [ 42 , 43 ], never the less, telehealth content and experiences among different levels of nursing education appeared to remain low [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four of the studies reported including experienced nurses in the field of chronic disease management [ 6 , 30 , 31 , 33 ], one included a nurse manager [ 34 ], two studies highlighted the need to have the nurses go through a special course on cultural competency [ 32 ] and formal training on telephone health coaching [ 35 ] prior to participating in the study. Other studies have reported that Registered Nurses (RN) have the undergraduate preparation to promote healthy lifestyles, prevent the development of disease and deliver care and follow-up to different health conditions on community heath setting [ 42 , 43 ], never the less, telehealth content and experiences among different levels of nursing education appeared to remain low [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although HBPT has been used extensively in various patient populations with hypertension [59][60][61][62][63][64] , only a few studies have assessed the benefits of HBPT for BP control and other outcomes assessment in patients with CKD. In the Telemonitoring and Self-Management in Hypertension 4 (TASMINH4) trial, after 12 months, adjusted SBP mean differences (self-monitoring and telemonitoring groups) vs. usual care was -3.5 mmHg [95%CI: -5.8 to -1.2] and -4.7 mmHg [-7.0 to -2.4]), respectively [64] .…”
Section: Home Bp Telemonitoring In Ckd Populationsmentioning
confidence: 99%
“…Of 175 international systematic reviews identified in PubMed (date of search: 9 December 2022), 10 potentially relevant reviews described impact on glycaemic control,17–20 diabetic ketoacidosis21 and interventions to recover or sustain diabetes or hypertension care 22–26. Overall, improvements in glycaemic control were seen in high-income countries during the pandemic, likely reflecting a high motivation for diabetes self-management due to associations with COVID-19 outcomes, supportive care through teleconsultations, and easier meal-planning, improved sleep habits and reduced access to fast food when staying at home during movement restrictions 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…Four systematic reviews reported on interventions to sustain diabetes or hypertension care during the COVID-19 pandemic internationally,22 23 25 26 and one review protocol was identified 24. Telehealth and home visits were mentioned as modalities to manage diabetic foot conditions 25.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation